COMPARISON OF THE DIAGNOSTIC ACCURACY OF MAGNETIC RESONANCE IMAGING AND ULTRASOUND EXAMINATION FOR X-RAY NEGATIVE STAGE OF KNEE JOINTS OSTEOARTHRITIS - M. V. Makarova; M. Yu. Valkov (Исследования и практика в медицине)
Purpose. To compare of the diagnostic accuracy of ultrasonography (US) with magnetic resonance imaging (MRI) as a reference in the assessment of pathological changes of the soft tissues at the X-ray negative stage of knee joint osteoarthritis (OA).Materials and methods. Nineteen patients with X-ray negative stage of knee OA diagnosed in 2015 underwent US and MRI of the knee joints. We estimated the sensitivity and speciﬁcity, positive and negative predictive values for pathological changes in 7 distinct anatomical areas on US comparing to MRI.Results. There were no false positive results. The ﬁndings of US and MRI coincided for the presence of an excess amount of free ﬂuid in the joint cavity and suprapatellar bursa synovitis and the presence of Baker’s cyst, 15 (79%) and 4 (21%) patients, respectively. More o en, false-negative results on US have been seen in assessing changes in the lateral meniscus and osteophytes: 2 (11%) diagnosed cases vs 15 (79%) for MRI, respectively. The degenerative changes in the medial meniscus were found in 10 (52.6%) on US compared to 15 (79%) for MRI, respectively. Method of US showed the low sensitivity in the detection of early pathological changes of the knee ligaments: sensitivity and predictive value of negative results accounted for the cruciate were 47% and 18%, for collateral ones only 24% and 13%, respectively.Conclusion. Ultrasound examination is highly eﬀective in the diagnosis of synovitis, free ﬂuid in the joint cavity and suprapatellar bursa and Baker’s cysts in patients with X-ray negative stage of knee OA. It helps to identify the group of patients with the highest risk of progression of OA. The method of ultrasound is signiﬁcantly inferior to MRI in the diagnosis of early degenerative changes in ligaments, the menisci and cartilage of the joint.